Tolerance Developing in Early Childhood Education Based Child-Friendly School - Jumiatmoko, Jumiatmoko; Dwiningrum, Siti Irene Astuti; Harun, Harun; Syamsudin, Amir (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2024)
The development of tolerance is the main component of Early Childhood Education in Child-Friendly Schools (ECE-CFS). This study aimed to examine the types and quantity distribution of best practices implemented by ECE-CFS to develop tolerance in early childhood. This research used a qualitative approach involving 102 (one hundred and two) ECE-CFS teachers as respondents. Respondents answered 5 questions via Google Forms. Data were analyzed using the open coding and axial coding approach of the Corbin & Strauss model. The results show 19 (nineteen) types of best practices in developing tolerance in ECE-CFS. The dominant types include habituation activities, providing examples, and organizing special activities. The perspective of progressivism philosophy, the characteristics of an emancipatory curriculum, and the optimization of social capital are discussed to provide recommendations to develop tolerance in ECE-CFS.